Cervical human papillomavirus infection in women with preterm prelabor rupture of membranes - Hornychova, Helena; Kacerovsky, Marian; Musilova, Ivana; Pliskova, Lenka; Zemlickova, Helena; Matejkova, Adela; Vosmikova, Hana; Rozkosova, Katerina; Cermakova, Petra; Bolehovska, Radka; Halada, Petr; Jacobsson, Bo; et al. (PloS one, 2018)
OBJECTIVE: To evaluate the association between cervical human papillomavirus (HPV) infection at the time of admission and the presence of microbial invasion of the amniotic cavity (MIAC) and intra-amniotic inflammation (IAI) in women with preterm prelabor rupture of membranes (PPROM) and to determine the association between cervical HPV infection and short-term neonatal morbidity. METHODS: One hundred women with singleton pregnancies complicated by PPROM between the gestational ages of 24+0 and 36+6 weeks were included in the study. The presence of HPV DNA was evaluated in scraped cervical cells using polymerase chain reaction (PCR). Amniotic fluid samples were obtained by transabdominal amniocentesis. RESULTS: The rate of cervical HPV infection in women with PPROM was 24%. The rates of MIAC and IAI were not different between women with cervical HPV infection and those without cervical HPV infection [MIAC: with HPV: 21% (5/24) vs. without HPV: 22% (17/76), p = 1.00; IAI: with HPV: 21% (5/24) vs. without HPV: 18% (14/76), p = 0.77]. There were no differences in the selected aspects of short-term neonatal morbidity between women with and without cervical HPV infection. CONCLUSIONS: In women with PPROM, the presence of cervical HPV infection at the time of admission is not related to a higher risk of intra-amniotic infection-related and inflammatory complications or worse short-term neonatal outcomes.
Keywords: Papillomaviridae; kojenecká mortalita; Fetal Membranes, Premature Rupture; těhotenství; kojenec; příjem pacientů; plodová voda; cervix uteri; Papillomavirus Infections; Infant; Adult; Amniotic Fluid; Infant, Newborn; infekce papilomavirem; ženské pohlaví; novorozenec; Humans; Pregnancy; předčasný odtok plodové vody; Infant Mortality; Patient Admission; dospělí; Female; Cervix Uteri; lidé